Penggunaan bakteri probiotik untuk pencegahan infeksi bakteri Streptococcus agalactiae pada ikan Nila, Oreochromis niloticus - Umasugi, Aisin; Tumbol, Reiny A.; Kreckhoff, Reni L.; Manoppo, Henky; Pangemanan, Novie P.L.; Ginting, Elvi L. (Universitas Sam Ratulangi, 2018)
This study aimed to evaluate the effect of probiotic on growth and survival of tilapia (Oreochromis niloticus) against Streptococcus agalactiae infection. The test materials used were commercial probiotic bacteria and Streptococcus agalactiae. The probiotic bacteria were administered by mixing into the feed with a dose of 0 mL (without probiotics), 10 mL / kg of feed, 15 mL / kg of feed and 20 mL / kg of feed. Feed was given 3 times a day at 08.00, 12.00 and 16.00 for 21 days. After that, the challenge test was done with Streptococcus agalactiae bacteria by cohabitation. Bacteria with a density of 107 cells / mL were mixed into the water and allowed for 2 hours. The result showed that B treatment (10 mL / kg of feed) gave the best result with 93,33 percent of survival rate. Statistical analysis showed that the survival of fish in treatments B, C and D was significantly different from treatment A (P <0.1). However, there was no significant difference between treatments B, C, and D. It was also found that the addition of probiotic in feed did not affect the growth of Nile tilapia (Orechromis niloticus). Keywords : Probiotic bacteria, nile tilapia, Streptococcus agalactiae, growth, infection